Combining Intersemiotic and Interlingual Translation in Training Programmes: A Functional Approach to Museum Audio Description - Bartolini, Chiara; Manfredi, Marina (Status Quaestionis, 2022)
This paper seeks to put forward a didactic proposal focused on museum audio description (AD) to be implemented with post-graduate students attending a translation studies course within a Languages and Communication programme. The aim is to raise students’ awareness of translation and accessibility practices in the cultural and creative industries and train specialised translators and describers. The proposal includes two different but complementary levels. On a more theoretical side, museum AD is introduced, both as a form of intersemiotic translation and as an interpretative tool in the museum’s wider communication framework. From a practical point of view, we draw on Mazur (2020), who exploited the functional model proposed by Nord (2018 [1997]) with her translation-oriented text analysis in the context of screen AD training. We suggest that it may also be adapted to serve as a guiding methodology for prospective museum translators and describers. In doing so, intersemiotic translation is combined with interlingual translation to train students to (1) audio describe specific artworks/artefacts in their first language (L1) and (2) translate the produced ADs into their second language (L2).